Changes in Lipid Metabolites and Enzyme Activities of Wheat Flour during Maturation - Yanyan Chen; Yingtao Yu; Xin An; Huihui Zhang; Wei Gong; Ying Liang; Jinshui Wang (Foods, 2024)
The maturation of wheat flour is a transformative process that elevates its processing and culinary attributes to their peak performance levels. Despite extensive research on starch and gluten protein modifications, the impact of lipid changes has been largely unexplored. This study addresses this gap by examining the maturation of freshly milled wheat flour at 15 °C, 25 °C, and 40 °C over 60 days, focusing on enzymatic activities—lipase, lipoxidase, and catalase—and lipid metabolites, including free fatty acids, conjugated trienes, p-anisidine value, and total oxidation value. The results of this study showed that free fatty acids continued to increase at all temperatures, with the most significant increase of 50% at 15 °C. The p-anisidine value followed a pattern of initial increase followed by a decline, while conjugated trienes were markedly higher at 40 °C, suggesting temperature’s significant influence on lipid peroxidation. Notably, total oxidation values became erratic post 30 days, indicating a shift in oxidative dynamics. This study underscores the correlation between lipid metabolites and enzymatic activities, revealing the enzymes’ pivotal role in lipid oxidation. The interplay of temperature and time offers valuable insights for optimizing wheat flour maturation, ensuring superior quality for various applications.